Improving the Fifth Grade Students’ Activities and Learning Outcomes of Civics Subject by Using Inquiry Approach in Semester 2 of 2018/2019 Academic Year at SDN Karangsemanding 02 Jember - Setyagung Budi Cahyono (Pancaran Pendidikan, 2020)
In learning, students often face social problems and the teacher does not try to solve the problems through the implementation of learning approach. Therefore, a learning approach that is able to develop social relationship needs to be created to make the learning more enjoyable. Learning in the setting of “teacher directed” or the one which combines the learning environment called “self-directed”. Thus, inquiry model which specifically used in this research called social inquiry is expected to be able to make the teacher know the learning problem in Civics subject and then take steps to solve it. Based on the result of the research, it was known that there was an improvement in terms of quality in the activities and learning outcomes on the fifth grade students at SDN Karangsemanding 02 Balung district, Jember regency in 2018/2019 academic year. There was a considerable raise in the graphic. The classical achievement in pre-cycle which was 58.6% increased to 82.75% in cycle I and 96.55% in cycle II. Meanwhile, the average score of the class increased from 67 in cycle I to 74 in cycle II.